Personal Monitor for Evaluation of Human Functional State - Korsakas, S.; Vainoras, A.; Gargasas, L.; Jurkonis, V.; Ruseckas, R.; Miškinis, V.; Jurkonienė, R.; Vitartaitė, A. (Elektronika ir Elektrotechnika, 2007)
The aim of this work was to develop algorithms and software for personal monitor of human functional state evaluation. Two software packages were developed: one – for continuous on-line analysis of monitored vital signals (ECG, motion activity) with the generation objective feedback to patient and second - for comprehensive off-line analysis of storage data during long-term (24 hours) patient monitoring for diagnostic purposes. The method of breathing frequency evaluation from ECG parameters was developed. One investigation for sportsmen during physical load showed the good agreement with real situation. The developed personal monitor with software for patient functional state evaluation is required to test according standard IEC 60601-2-47:2001 for monitoring heart failure patients at home conditions. Ill. 10, bibl. 6 (in English; summaries in English, Russian and Lithuanian).